Health Technology Assessment’s Italian Network: origins, aims and advancement (Italian Journal of Public Health, 2005)
The Italian National Health Care Service, as many other industrialised countries’, has to cope with increasinghealth care needs in spite of limited resources available.Therefore, it is necessary to assess diagnostic-therapeutic procedures, technologies and organizationalstandards, in order to allocate the available resources appropriately.Health Technology Assessment provide scientific support to the policies that all countries have adopted inorder to rationalize, and sometimes to ration, health care services.Since in Italy dissemination and utilisation of HTA as means to support health care policies are still limited,in 2003 The Ministry of Health Care, within the development of Special funding Programmes – art.12 bis,comma 6, Law 229/99n. – , financed the establishment of an HTA Italian network, in order to foster the appli-cation of principles of technologies’ management in health care organisations.
Keywords: network; Health Technology Assessment; standards